2013
DOI: 10.1614/ws-d-12-00076.1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Indigenous Fungal Pathogens from Horse Purslane (Trianthema portulacastrum) for Their Relative Virulence and Host Range Assessments to Select a Potential Mycoherbicidal Agent

Abstract: Periodic surveys were conducted to seek potential indigenous fungal agents for development as mycoherbicides against horse purslane, a major weed of agricultural fields in India. Pathogenic fungal species were isolated and identified from naturally infected horse purslane. The biocontrol potential of these pathogens for horse purslane was evaluated by studying their host range and virulence under growth chamber and greenhouse conditions. Three candidates,Alternaria alternata, Fusarium oxysporum, andPhoma herba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…and Pythium spp. ; the host spectrum of which being particularly wide can include weeds as well as crops (Agrios 1997;Berestetskiy 2004;Pane et al 2011;Ray and Vijayachandran 2013).…”
Section: Biotic Interactions Between Fungi and Weeds At Various Weed mentioning
confidence: 99%
“…and Pythium spp. ; the host spectrum of which being particularly wide can include weeds as well as crops (Agrios 1997;Berestetskiy 2004;Pane et al 2011;Ray and Vijayachandran 2013).…”
Section: Biotic Interactions Between Fungi and Weeds At Various Weed mentioning
confidence: 99%
“…Infected leaves collected from various sites, yielded a species of Gibbago, identified as Gibbago trianthemae Simmons, a phaeodictyoconidial hyphomycetes fungus reported on horse purslane for the first time in India. Pathogenicity of some fungal pathogens on horse purslane was studied in earlier; the species of fungal pathogens namely Cercospora trianthemae (Chiddarwar,1962), Drechslera (Exserohilum) indica (Bipolaris indica) (Rao and Rao, 1987;Taber et al, 1988), Colletotrichum gloeosporioides (Darshika and Daniel, 1992), Fusarium oxysporum (Darshika and Daniel, 1992;Ray and Lakshmi, 2013), Fusarium semitectum (Darshika and Daniel 1998), Alternaria alternata (Bohra et al, 2005;Gupta and Mukerji, 2001;Ray and Lakshmi, 2013), Paecilomyces varioti Bain. (Babu et al, 2004), Myrothecium verrucaria (Albertini and Schwein) Ditmar.…”
Section: Discussionmentioning
confidence: 99%
“…(Babu et al, 2004), Myrothecium verrucaria (Albertini and Schwein) Ditmar. Fr., (Boyette and Abbas, 2001), Phoma herbarum Westendorp (Ray and Lakshmi, 2013), Fusarium chlamydosporum Wollenw. & Reinking (Aneja et al, 2014) and Gibbago trianthemae Simmons (Simmons, 1986;Mitchell, 1988;Aneja and Kaushal, 1998;Aneja et al, 2000;Akhtar et al, 2013) have been identified around the world, of these Gibbago trianthemae have shown potential to control of this weed.…”
Section: Discussionmentioning
confidence: 99%
“…HP (horse purslane) is a very noxious annual herbaceous weed. It is considered as a one principle weed in various field crops, such as mustard, soybean, cotton and maize ( Nayyar et al, 2001 ; Ray and Vijayachandran, 2013 ). It belongs to the Aizoaceae family.…”
Section: Introductionmentioning
confidence: 99%